Using Benefit Sought Variables for Soft Drinks Consumers Segmentation-Case Study City of Pristina - Begunca, Arsim (European Journal of Economics and Business Studies, 2016)
Soft drinks market is a very large and important market where competition is very fierce. In recent years this market in global terms has not greatly increased. Thus for all the actors of this market without understanding (recognition) of the customer/consumer, they may lose a market share from competitors given the fierce competition. The purpose of this study is the identification of market segments within the city of Prishtina regarding soft drinks consumers based on requiredbenefits /benefits sought. The result of this study supports the effectiveness of soft drinks consumer segmentation using the required benefit variables. Statistical Package for Social Science program ( SPSS version 20 ) was used for data analysis. This study used a descriptive analysis, factor analysis and cluster analysis. Based on differentiating factors in selecting soft drinks (refreshments), social-demographic variables and soft drinks consumer behavior throughout theses segments, the managers can modify their marketing strategies to fulfil the needs of these segments and at the same time maximize the profit.
Keywords: benefit sought, soft drinks